Opportunities and Challenges for Research on Heat Recovery from Wastewater: Bibliometric and Strategic Analyses - Sabina Kordana-Obuch; Michał Wojtoń; Mariusz Starzec; Beata Piotrowska (Energies, 2023)
The potential for recovering heat from wastewater exists at various stages, including generation, transport, and treatment. As a result, various technologies for thermal energy recovery from wastewater are now successfully employed in many countries. In order to synthetically present the current state of knowledge on heat recovery from wastewater, a bibliometric analysis of previously published studies indexed in the Web of Science database was performed. The review was further extended with strategic SWOT and SOAR analyses to identify internal and external factors determining the competitive advantage and weaknesses related to the use of wastewater heat exchangers and heat pumps. These analyses indicated the need for further research on the possibilities of heat recovery from wastewater as the use of this technology, both at the building level and on a larger scale, contributes to the implementation of sustainable development goals, especially in terms of improving energy efficiency and reducing CO2 emissions. Particular emphasis should be placed on research into the use of warm wastewater together with other, better known and accepted, renewable energy sources. It is also important to continuously educate the public and promote heat recovery technologies at various levels, as well as to increase the involvement of legislators and other stakeholders.